COMPARATIVE ANALYSIS OF THE TREATMENT OF PATIENTS WITH DYSPLASTIC AND IDIOPATHIC OSTEOARTHROSIS OF THE HIP JOINT - Yurchenko, Denys; Klymovytskyi, Fedor; Goncharova, Larysa; Tiazhelov, Oleksiy; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Hip arthroplasty is a reliable and quick way to relieve the patient of pain, restore movement in the hip joint and improve the function of the affected limb, but the question of how effective this intervention is in dysplastic or idiopathic coxarthrosis requires further study. The objective of the study was to evaluate the effectiveness of treatment of patients with idiopathic and dysplastic coxarthrosis, and the effect of endoprosthetics on the work of the pelvic muscles. Methods. A comparative analysis of the treatment of 121 patients was conducted, which were divided into two groups — with dysplastic coxarthrosis (63 patients) and with idiopathic coxarthrosis (58 patients). The functional results of the treatment were studied according to the Harris scale, the data of stabilographic studies and the evaluation of the work of the muscles of the pelvic girdle, which are responsible for maintaining the horizontal balance of the pelvis. Results. In general, the results of endopros thesis were evaluated as good in both groups. At the same time, the average results in the group of patients with idiopathic coxarthrosis are significantly better (t = 2.08; p = 0.001) than in the group of patients with dysplastic coxarthrosis. However, the indicators of the muscles that ensure the horizontal balance of the pelvis, in most cases, remain reduced within 6–8 months after the endoprosthesis operation. This is evidenced by clinical data and statistical research data. Conclusions. Endoprosthesis of the hip joint is an effective method of coxarthrosis and allows to significantly improve both the patientʼs support and kinematic function and his quality of life. The results of treatment of patients with idiopathic coxarthrosis according to the Harris scoring scale are significantly better than the results of treatment of patients with dysplastic coxarthrosis. But the performance indicators of the muscles of the pelvic girdle, in most cases remain reduced within 6–8 months after endoprosthesis surgery in patients of both groups.